2021
DOI: 10.3390/ijerph18199998
|View full text |Cite
|
Sign up to set email alerts
|

A Vegan Diet Is Associated with a Significant Reduction in Dietary Acid Load: Post Hoc Analysis of a Randomized Controlled Trial in Healthy Individuals

Abstract: The composition of diet strongly affects acid–base homeostasis. Western diets abundant in acidogenic foods (meat and cheese) and deficient in alkalizing foods (fruits and vegetables) increase dietary acid load (DAL). A high DAL has been associated with numerous health repercussions, including cardiovascular disease and type-2-diabetes. Plant-based diets have been associated with a lower DAL; however, the number of trials exploring this association is limited. This randomized-controlled trial sought to examine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 43 publications
3
53
0
Order By: Relevance
“…Our study provides evidence that a high diet-dependent acid load is common in cancer survivors in the NHANES and emphasizes the need for additional research in this area of current oncological interest. It is of utmost importance to highlight that DAL is an easily modifiable risk factor, as dietary interventions promoting more plant-based diets were shown to reduce acid load from diet [ 5 , 68 , 69 ]. The fact that our results still revealed a higher acid load in cancer survivors (who most likely modified and improved their diet after diagnosis) as compared to the general population reinforces this call.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our study provides evidence that a high diet-dependent acid load is common in cancer survivors in the NHANES and emphasizes the need for additional research in this area of current oncological interest. It is of utmost importance to highlight that DAL is an easily modifiable risk factor, as dietary interventions promoting more plant-based diets were shown to reduce acid load from diet [ 5 , 68 , 69 ]. The fact that our results still revealed a higher acid load in cancer survivors (who most likely modified and improved their diet after diagnosis) as compared to the general population reinforces this call.…”
Section: Discussionmentioning
confidence: 99%
“…We described the employed methods for the calculation of DAL in our previous publications in detail [ 5 , 22 ]. In brief, we used the formulas developed by Remer & Manz and Frassetto et al to calculate Net Endogenous Acid Production (NEAP) [ 2 ] and Potential Renal Acid Load (PRAL) from diet [ 6 , 46 , 47 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We hypothesized that SAM and SAH concentration in human plasma may vary upon transition from an omnivorous diet into a vegan or meat-rich diet. To test the effect of a plant-based diet on SAM and SAH metabolism, we examined SAM and SAH concentrations in the plasma and urine of a well-characterised cohort of healthy omnivorous adults participating in a randomised controlled trial (RCT) with an intervention with either a vegan or a meat-rich diet (VD and MD, respectively) for 4 weeks [ 36 , 37 , 38 , 39 ]. Our study revealed similar variations in SAM and SAH concentrations from baseline to end of trial in the plasma and urine of healthy adults, regardless of dietary pattern.…”
Section: Introductionmentioning
confidence: 99%